ANALISIS PENGUATAN KINERJA KARYAWAN - Firdaus Na; Tjiptogoro Dinarjo Soehari (Akademika, 2019)
Research aims to understand the influence of competence, training and career development simultaneously and partial of the performance of employees PT.Kharisma Potensia Indonesia in Jakarta. The kind of research to research this is explanatory research. The size of the population in this research was 55 employees and The sampling method used is a saturated sampling. Variable free is competence ( X1 ), training ( X2 ) and career development ( X3 ), while variable their lack of roots is a an employee ( y ).Equation of Multiple Linear Regression Y = 0,450+ 0,278x1 + 0,258x2 + 0,402x3 + e; Rsquare = 0,403; F = 11,498, Career development is the most dominant factor in employee performance. Competence, training and career development have a positive and significant influence on employee performance. The results of employee performance are 0.450, If X1, X2, and X3, are considered zero, it will affect employee performance of 0.450 if the 1-5 Likert scale is included in the not too good category.